Positive Association between Tinnitus and Arterial Hypertension - Figueiredo, Ricardo Rodrigues; Azevedo, Andréia Aparecida; Penido, Norma De Oliveira (Frontiers in Neurology, 2016)
Introduction: Tinnitus is the perception of noise in the absence of an external source and is considered by most authors as a multifactorial symptom. A systematic review concerning the association of tinnitus and systemic arterial hypertension retrieved suggestions of a positive association, but the articles included failed to perform a detailed analysis on the theme. Purpose: To analyze the presence of arterial hypertension in tinnitus and non-tinnitus patients. To analyze differences between tinnitus impact and psychoacoustic measurements in hypertensive and normotensive patients and to evaluate the association between the presence of tinnitus and the diverse antihypertensive drugs employed. Material and method: Cross-sectional transversal study, comparing two groups of subjects ( 144 in the study group with tinnitus and 140 in the control group, without tinnitus). Clinical, demographical, audiometrical and psychoacoustics characteristics of the subjects were compared. Results: Hypertension prevalence in tinnitus subjects was 44.4% against 31.4% in subjects without tinnitus (p=0.024). Positive associations with tinnitus were found with hypertension treatment with angiotensin-converting enzyme inhibitors ( p=0.006), tiazidic diuretics (p<0,0001), potassium-sparing diuretics ( p=0.016) and calcium channels blockers (p=0.004). Conclusions: There is an association between tinnitus and arterial hypertension. This association is particularly strong in older patients. Hypertension treatment with diuretics, angiotensin-converting enzyme inhibitors and calcium channels blockers was more prevalent in tinnitus patients, suggesting that an eventual ototoxicity of these drugs may be involved in tinnitus pathophysiology, a hypothesis that should be evaluated in further studies.